THE RELATIONSHIP BETWEEN PROFESSIONAL IMAGE AND PEDAGOGICAL COMPETENCE (Eureka Journal of Education & Learning Technologies, 2026)
This study explores the relationship between professional image and pedagogical competence in the context of teacher education. The professional image of a teacher is considered a significant factor influencing not only students’ perceptions but also the overall effectiveness of the educational process. In modern educational environments, pedagogical competence encompasses a range of skills, including subject knowledge, communication abilities, ethical behavior, and reflective practice.
Keywords: Professional image, pedagogical competence, teacher education, future teachers, professional development, teaching effectiveness, communication skills, professional ethics, reflective practice, educational environment.